A Core Sampler for Puddled Soils - Sharma, P.K.; De Datta, S.K. (Wiley, 1985)
A core sampler was designed to collect undisturbed samples of known volume from the 0‐ to 10‐cm depth in soft‐puddled soils. The instrument is simple, inexpensive to construct, and easy to operate. With practice, the operator can routinely collect a sample from flooded, puddled soils in < 2 min.